Computed tomography and magnetic resonance imaging in assessment of the local advancement of oral and oropharyngeal cancer as the key factor of treatment selection (literature review) - Ye. O. Osipyan; A. M. Mudunov (Опухоли головы и шеи, 2018)
Oral and oropharyngeal tumors are the most frequent cancers in the head and neck region. Despite their visual localization, the majority of cases is diagnosed at advanced stages. The treatment should be planned only after assessment of all pathways of tumor advancement taking into account anatomical characteristics of the area. In this review, diagnostic criteria affecting the method and extent of surgical treatment and the role of computed tomography and magnetic resonance imaging in their assessment are presented.